UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN BACA TULIS AL QURAN PADA PESERTA DIDIK DI SMP NEGERI 3 CILELES KABUPATAN LEBAK - rasikin, rasikin; Jubaedah, Siti; Ahdawiyah, Siti (Staisman Press, 2021)
This research was conducted at Cileles Public Middle School 3, Lebak Regency in 2019. This research is a type of qualitative research based on data in the field and supporting documents. This study also contains data from interviews with Al-Qur'an reading and writing teachers, documentation and results of observations that the author conducted at SMP Negeri 3 Cileles, Lebak Regency. While the data collection method used in this study are: interview method, observation method and documentation method. Based on the results of the study it can be seen that the efforts made by the teacher in improving the quality of students' reading and writing of the Qur'an are: 1) adding hours of study for 2 hours per week with the Iqro Quran program, 2) using appropriate methods according to the level of student ability including the habituation method (drill), 3) applying appropriate media to learning to read and write the Koran, 4) finding and providing BTA materials and giving homework (PR), and 5) providing learning facilities and infrastructure.